Effect of Dialkyl Peroxide Blending on Tensile Properties of PLA/PBAT Polymer Alloys - NISHIDA, Masahiro; ICHIHARA, Hiroki; WATANABE, Hiroki; FUKUDA, Norio; ITO, Hiroaki (Engineering Transactions, 2012)
Poly(lactic acid) (PLA) and poly(butylene adipate/terephthalate) (PBAT) were used for polymer alloys, and the effects of the mixing ratio of PLA and PBAT and the addition of dialkyl peroxide (compatibilizing agent) were examined. The stress-strain curves of PLA/PBAT and PLA/PBAT/dialkyl peroxide specimens were measured using a tensile split Hopkinson bar (Kolsky Bar) method and a universal testing machine. The mixing ratio of PLA and PBAT and the dialkyl peroxide addition affected the shape of the stress-strain curve behavior. Regardless of the strain rate, the yield stress decreased and the elongation at break and strain energy increased with increasing PBAT content when the dialkyl peroxide was used. At high strain rate, the dialkyl peroxide addition increased the elongation at break and the strain energy, and changed the fracture surface to a whitened form that was markedly uneven. This result could explain the improvement in the Izod impact strength.